2006
DOI: 10.1159/000092857
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Oligonucleotide Microarray Analysis on Placentae of Pre-Eclamptic Pregnancies

Abstract: Objective: Human placentae from normal and pre-eclamptic pregnancies were evaluated for possible changes in gene expression by microarray analysis to uncover new clues for the research of the etiology of pre-eclampsia. Methods: Placentae from five normal pregnancies and five pregnancies complicated by pre-eclampsia were collected. mRNA levels of five pre-eclamptic placentae were examined using genome-wide 70-mer oligonucleotide microarrays (CapitalBio, Beijing, China) in comparison with the pooled control cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
1
27
1
1
Order By: Relevance
“…Higher methylation was also observed in some genes in the preeclampsia (Jia et al 2012). Here, we showed that the differentially expressed genes in preeclampsia placental tissues were mainly enriched in several pathways associated with pregnancy maintenance, metabolism, oxidative stress and oxidative metabolism, cell cycle regulation, embryogenesis and development, implantation, placentation and decidualization, immune modulation, and vascular function (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012). We summarized the major functional categories on the differential gene expression profile between preeclampsia and normal placentas ( Table 1).…”
Section: Preeclampsia Susceptibility Genesmentioning
confidence: 82%
See 1 more Smart Citation
“…Higher methylation was also observed in some genes in the preeclampsia (Jia et al 2012). Here, we showed that the differentially expressed genes in preeclampsia placental tissues were mainly enriched in several pathways associated with pregnancy maintenance, metabolism, oxidative stress and oxidative metabolism, cell cycle regulation, embryogenesis and development, implantation, placentation and decidualization, immune modulation, and vascular function (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012). We summarized the major functional categories on the differential gene expression profile between preeclampsia and normal placentas ( Table 1).…”
Section: Preeclampsia Susceptibility Genesmentioning
confidence: 82%
“…This review provides a detailed overview of typical genome-wide studies that have been conducted so far on preeclamptic placental tissue samples (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Therefore, defining the gene expression of preeclamptic placentas has been the focus of numerous studies (Damiano, 2011;Ornaghi et al, 2011;Shin et al, 2011;Wang et al, 2011). To our knowledge, a number of comprehensive analyses have been conducted on the gene expression in preeclamptic placentas using DNA microarrays Pang and Xing, 2003a, 2003b, 2004Reimer et al, 2002;Sitras et al, 2009;Tsoi et al, 2003;Zhou et al, 2006). These studies revealed a substantial number of molecular players involved in the process of preeclampsia development, and helped defined the role of some of the signaling pathways involved in the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of microarray studies have been conducted on placental gene expression in preeclampsia and showed that obesity-related genes, cytokine-receptor genes, and apoptosis-related genes are involved in the development of preeclampsia (Centlow et al, 2011;Gack et al, 2005;Han et al, 2006;Heikkila et al, 2005;Herse et al, 2007;Kang et al, 2011;Lee et al, 2010a;Nishizawa et al, 2007;Pang and Xing, 2003a;Reimer et al, 2002;Sitras et al, 2009;Soleymanlou et al, 2005;Tsoi et al, 2003;Zhou et al, 2006;Zhu et al, 2002). However, comparison of different studies done using DNA microarrays has shown poor overlap, and only a minority of differentially-expressed genes are thus shared between them.…”
mentioning
confidence: 99%
“…Although this approach has been used previously for the possible detection of new novel biomarker candidates [10,11,12,13,14,15,16,17,18,19,20], most of these studies were conducted in nonhomogenous collectives, which limited their usefulness or the conclusions that can be drawn from them.…”
Section: Introductionmentioning
confidence: 99%